2023
DOI: 10.3389/fnins.2023.1145251
|View full text |Cite
|
Sign up to set email alerts
|

The signal intensity variation of multiple sclerosis (MS) lesions on magnetic resonance imaging (MRI) as a potential biomarker for patients’ disability: A feasibility study

Abstract: IntroductionAlthough many lesion-based MRI biomarkers in multiple sclerosis (MS) patients were investigated, none of the previous studies dealt with the signal intensity variations (SIVs) of MS lesions. In this study, the SIVs of MS lesions on direct myelin imaging and standard clinical sequences as possible MRI biomarkers for disability in MS patients were assessed.MethodsTwenty seven MS patients were included in this prospective study. IR-UTE, FLAIR, and MPRAGE sequences were employed on a 3T scanner. Region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
(64 reference statements)
2
5
0
Order By: Relevance
“…To avoid the lengthy acquisition time inherent to standard radial sampling in 3D UTE, an advantage can be taken of novel sampling strategies based on cone or stack-of-stars trajectories, as shown previously. [38][39][40]75 The average T 1 of lungs recorded in this study falls well within the expected range at B 0 = 9.4 T, at T 1 = 1101 ± 62 ms, and T 1 = 1078 ± 38 ms using nongated and motion-resolved images, respectively. Tibiletti et al 22 reported an average T 1 = 1500 ± 34 ms and T 1 = 710 ± 14 ms at B 0 = 7 T using global and selective inversion recovery, respectively.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…To avoid the lengthy acquisition time inherent to standard radial sampling in 3D UTE, an advantage can be taken of novel sampling strategies based on cone or stack-of-stars trajectories, as shown previously. [38][39][40]75 The average T 1 of lungs recorded in this study falls well within the expected range at B 0 = 9.4 T, at T 1 = 1101 ± 62 ms, and T 1 = 1078 ± 38 ms using nongated and motion-resolved images, respectively. Tibiletti et al 22 reported an average T 1 = 1500 ± 34 ms and T 1 = 710 ± 14 ms at B 0 = 7 T using global and selective inversion recovery, respectively.…”
Section: Discussionsupporting
confidence: 75%
“…By extending the imaging to 3D, it would be possible to further reduce the echo time at the expense of prolonged acquisition time. To avoid the lengthy acquisition time inherent to standard radial sampling in 3D UTE, an advantage can be taken of novel sampling strategies based on cone or stack‐of‐stars trajectories, as shown previously 38‐40,75 . The average T 1 of lungs recorded in this study falls well within the expected range at B 0 = 9.4 T, at T 1 = 1101 ± 62 ms, and T 1 = 1078 ± 38 ms using nongated and motion‐resolved images, respectively.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…With the rapid advancement of computer technology in recent years, new possibilities in MRI have emerged, including the accurate segmentation of the gray and white matter of the brain. These novel approaches hold tremendous promise for advancing the field of neuroscience and have led to numerous landmark findings ( 21 - 23 ). Conventional imaging methods have limitations in resolution, which makes it difficult to image small blood vessels in the brain.…”
Section: Discussionmentioning
confidence: 99%